Employers’ Relational Work on Social Media - Lindell, Eva; Crevani, Lucia (Nordic Journal of Working Life Studies, 2022)
Given how social media are commonly used in contemporary Nordic countries, social media platforms are emerging as crucial for relational work between employers, employees, and potential employees. By means of a discursive psychology approach, this study investigates employers’ constructs of relational work on social media through the use of two interpretative repertoires: the repertoire of loss of control and the repertoire of ever-presence. The consequences of these interpretative repertoires are a masking of power relations, especially between employers and young employees in precarious labor market positions and those with limited digital knowledge or financial means. Further, the positioning of social media as part of a private sphere of life means the invasion of not only employees’, but also managers’ private time and persona. The result of this study hence calls for the need to understand relational work on social media as part of normative managerial work.